Strategic Architecture in Poultry Company - Oktavia, Erlinda; Marimin, Marimin; Djohar, Setiadi (JDM (Jurnal Dinamika Manajemen), 2017)
The purpose of this study is to identify factors in the external environment affecting the poultry industry, analyze the business integration process of the company and know its internal factors, analyze the future of the poultry industry in Indonesia and formulate the strategic architecture of  PT Sierad Produce Tbk (SIPD) and its priority importance. Respondents in this study were determined using purposive sampling method. While the research method used is descriptive-qualitative with case study approach and using Analytical Hierarchy Process (AHP) as priority determination of interest.. The results of the research are several alternative SIPD strategy based on the main objective of the company, that is maximizing corporate integration, product development and market development. A strategic map as a strategic architecture design lane is created to illustrate the execution time of each alternative strategy. The business integration process at SIPD is currently not optimally developed, meaning that every stage of the production process is still a profit center. Achieving institutional markets with a contractual approach proves to ensure product survival.